The Budgeting and Economic Consequences of Ageing in The Netherlands - Roel Beetsma (Center for Economic Studies and ifo Institute (CESifo), 2001)
The costs of population ageing are primarily reflected in larger expenditures on pensions and health care. This paper explores the consequences of ageing for the Netherlands in a baseline scenario simulated with a dynamic general equilibrium model. We discuss the sensitivity of the results under alternative projections for population ageing. We explore also the effects of three types of social security reform: a reduction in benefits, an increase in the retirement age and smoothing of the public pension premium over time. We find that the welfare effects of ageing and the reforms are substantial.
Keywords: 330